The Rural Nonfarm Sector and Livelihood Strategies in Sri Lanka : Background Report to Sri Lanka Poverty Assessment (World Bank, Washington, DC, 2021)
Sri Lanka’s economy underwent steady structural transformation over the last two decades. During this time, economic activities increasingly shifted toward industry and services. Poverty fell significantly during this period, mainly led by nonfarm income growth. The nature of rural nonfarm activities is quite heterogeneous and nonfarm activities can entail low-return activities. Understanding the nature of the rural nonfarm economy is a first step towards assessing its potential to facilitate economic transformation and where policy interventions could be useful. The main findings are two-fold. First, there has been a clear shift from farm to nonfarm activities over the last decade, and livelihoods sources vary significantly across the income distribution. For example, poor households are much more likely to be engaged in farm activities or wage employment in industries, whereas rich households have a higher likelihood of working in services. While both farm and nonfarm activities are vital to support rural livelihoods, it is the nonfarm sector that engages the majority of rural workers. Second, better education is strongly associated with higher participation and payoff from nonfarm activities. Interestingly, education does not seem to influence the choice between engaging in farm and unskilled nonfarm employment, highlighting a possible skills barrier to moving to better-paying nonfarm jobs.